2017
DOI: 10.1126/science.aah5744
|View full text |Cite
|
Sign up to set email alerts
|

Combining polyethylene and polypropylene: Enhanced performance with PE/ i PP multiblock polymers

Abstract: Polyethylene (PE) and isotactic polypropylene (PP) constitute nearly two-thirds of the world's plastic. Despite their similar hydrocarbon makeup, the polymers are immiscible with one another. Thus, common grades of PE and PP do not adhere or blend, creating challenges for recycling these materials. We synthesized PE/PP multiblock copolymers using an isoselective alkene polymerization initiator. These polymers can weld common grades of commercial PE and PP together, depending on the molecular weights and archit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
484
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 467 publications
(510 citation statements)
references
References 27 publications
22
484
2
2
Order By: Relevance
“…Although the α-methylstyrene moiety remained intact during the CCTP performed using rac-[Me 2 Si(2-methylindenyl) 2 ]ZrCl 2 , it was sluggishly involved in the subsequent anionic styrene polymerization. Thus, we herein attempted the use of a dialkylzinc species bearing a styrene moiety instead of an α-methylstyrene moiety (i.e., 1 versus 3) in addition to the use of pyridylaminohafnium catalyst 4 instead of rac-[Me 2 Si(2-methylindenyl) 2 ]ZrCl 2 , as the former is reportedly a more efficient catalyst for the CCTP and prevents the undesirable β-elimination process [1,7,8,42,46,47]. It should also be noted that the styrene moiety did not interfere in the CCTP performed using 4.…”
Section: Strategy For the Preparation Of Ps-block-po-block-psmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the α-methylstyrene moiety remained intact during the CCTP performed using rac-[Me 2 Si(2-methylindenyl) 2 ]ZrCl 2 , it was sluggishly involved in the subsequent anionic styrene polymerization. Thus, we herein attempted the use of a dialkylzinc species bearing a styrene moiety instead of an α-methylstyrene moiety (i.e., 1 versus 3) in addition to the use of pyridylaminohafnium catalyst 4 instead of rac-[Me 2 Si(2-methylindenyl) 2 ]ZrCl 2 , as the former is reportedly a more efficient catalyst for the CCTP and prevents the undesirable β-elimination process [1,7,8,42,46,47]. It should also be noted that the styrene moiety did not interfere in the CCTP performed using 4.…”
Section: Strategy For the Preparation Of Ps-block-po-block-psmentioning
confidence: 99%
“…The subtle architecture of the PO chains is of particular interest in the bulk polyolefin industry. For example, sequence control to form olefin block copolymers (OBCs) is a formidable task in olefin polymerizations [1][2][3][4][5]. Following the commercialization of OBCs by the Dow Chemical Company [6][7][8], Coates et al recently reported the preparation of PE/iPP (iPP = isotactic polypropylene) multiblock copolymers to enhance capabilities of plastic recycling [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Living polymerization enables us to produce block copolymers by switching the monomer from one to the other during the polymerization [3,4,5,6,7,8]. The simplest and most widely studied type of block copolymer is diblock, where two building blocks of different natures are joined together by a single covalent bond.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, several noteworthy systems were introduced that led to the living and iso -specific polymerization and copolymerization of α-olefins [2,3,4,5]. For example, Coates et al reported that the pyridylamidohafnium catalyst system produced iso -PP- block -PE (polyethylene) diblock and multiblock copolymers with precise control of block length ( M n = 208,000, mmmm = 91%, T m = 133 °C) [8]. Busico et al reported the preparation of iso -PP- block -EPR (poly(ethene- co -propene)) using Kol's diamino bis(phenolate)zirconium (or hafunium) catalyst under “quasi-living” conditions ( M n = 216,000, mmmm = 97% T m = 143 °C) [9,10].…”
Section: Introductionmentioning
confidence: 99%